2022
DOI: 10.17219/acem/149229
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil-to-lymphocyte ratio as a predictor of inflammatory response in patients with acute kidney injury after transcatheter aortic valve implantation

Abstract: Olasińska-Wiśniewska A, Urbanowicz T, Grodecki K, et al. Neutrophil-to-lymphocyte ratio as a predictor of inflammatory response in patients with acute kidney injury after transcatheter aortic valve implantation [published online as ahead of print on May 12, 2022].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
(48 reference statements)
0
3
1
Order By: Relevance
“…[33][34][35] Simple parameters from whole blood count, including NLR, MLR and SIRI, were postulated to be related to atherosclerosis progression. [36][37][38][39][40][41][42] However, in our analysis, none of these indices were related to carotid artery occlusion, although we previously presented the prognostic value of MLR for collateral carotid artery involvement. 32 The significant difference between LUCs and lymphocyte, monocyte and neutrophil counts is based on the characteristics of the cells; LUC counts take into account activated cells, while other cell counts measure the concentration of the cells.…”
Section: Discussioncontrasting
confidence: 53%
“…[33][34][35] Simple parameters from whole blood count, including NLR, MLR and SIRI, were postulated to be related to atherosclerosis progression. [36][37][38][39][40][41][42] However, in our analysis, none of these indices were related to carotid artery occlusion, although we previously presented the prognostic value of MLR for collateral carotid artery involvement. 32 The significant difference between LUCs and lymphocyte, monocyte and neutrophil counts is based on the characteristics of the cells; LUC counts take into account activated cells, while other cell counts measure the concentration of the cells.…”
Section: Discussioncontrasting
confidence: 53%
“…Olasinska-Wisniewska et al 19 also discovered that NLR increased significantly after TAVI in both the lowest and highest quartiles, with the increase being significantly greater in patients who developed AKI (median NLR of 8.3 vs. 4.9, p= 0.005). Another study by Olasinska-Wisniewska et al 20 revealed that NLR was decreased significantly after TAVI. We also found that the post-procedural NLR≥ 5.7 was an independent risk factor for AKI.…”
Section: Discussionmentioning
confidence: 93%
“…[15][16][17] Following TAVI, the NLR has been linked to the development of AKI. [18][19][20] The average platelet volume (MPV) is a computerized measurement of platelet size. As a result of increased platelet size, an increased MPV indicates larger, more reactive platelets.…”
Section: Introductionmentioning
confidence: 99%
“…However, using such markers in clinical practice is not possible, as a profound analysis of inflammatory phenomena is challenging and not costeffective. 18,19 Hence, simpler methods, such as whole blood analysis, were introduced and described as sufficient for demonstrating complex changes in the inflammatory response to cardiovascular disorders and predicting adverse outcomes or diminished survival. The results of whole blood analysis are readily available, and the method is repeatable, which gives it an advantage over other methods.…”
Section: Introductionmentioning
confidence: 99%